2018
DOI: 10.7554/elife.31919
|View full text |Cite
|
Sign up to set email alerts
|

Dengue viruses cleave STING in humans but not in nonhuman primates, their presumed natural reservoir

Abstract: Human dengue viruses emerged from primate reservoirs, yet paradoxically dengue does not reach high titers in primate models. This presents a unique opportunity to examine the genetics of spillover versus reservoir hosts. The dengue virus 2 (DENV2) - encoded protease cleaves human STING, reducing type I interferon production and boosting viral titers in humans. We find that both human and sylvatic (reservoir) dengue viruses universally cleave human STING, but not the STING of primates implicated as reservoir sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 99 publications
(151 reference statements)
3
80
0
Order By: Relevance
“…Consistent with this, some immune inhibitors are only effective against their native host species, thereby defining the viral host range (e.g. Parisien, Lau and Horvath, 2002;Mariani et al, 2003;Goffinet et al, 2009;Rajsbaum et al, 2012;van Mierlo et al, 2014;Stabell et al, 2018). We tested whether the immunosuppressive function of gp83 is conserved, and whether gp83 acts in a species-specific manner.…”
Section: Immunosuppressive Function Of Gp83 Depends On Conserved Resimentioning
confidence: 92%
“…Consistent with this, some immune inhibitors are only effective against their native host species, thereby defining the viral host range (e.g. Parisien, Lau and Horvath, 2002;Mariani et al, 2003;Goffinet et al, 2009;Rajsbaum et al, 2012;van Mierlo et al, 2014;Stabell et al, 2018). We tested whether the immunosuppressive function of gp83 is conserved, and whether gp83 acts in a species-specific manner.…”
Section: Immunosuppressive Function Of Gp83 Depends On Conserved Resimentioning
confidence: 92%
“…Not surprisingly, several viruses such as influenza virus, hepatitis C virus, and coronavirus [52,[54][55][56] have developed targeted evasion mechanisms to interfere with this pathway. The involvement of cGAS and STING in the innate immune response against DENV has become evident over the last few years, with several reports showing that DENV actually modulates this pathway (see below) [54,[57][58][59]. While it remains unclear how a DNA-binding protein, like cGAS, can detect viral RNA, it was recently suggested that the sensing of DENV infection rather occurs indirectly.…”
Section: The Dna Sensing Pathway and Denv Infectionmentioning
confidence: 99%
“…Indeed, DENV NS2B marks cGAS for lysosomal degradation and DENV NS2B-NS3 protease cleaves STING to suppress type I IFN induction [54,58,114,115]. Interestingly, DENV NS2B3 cannot process either mouse or nonhuman primate STING orthologs, suggesting that this pathogen has evolved towards an optimal pathogenicity in its natural hosts [54,59]. Very recently, it has been reported that DRP1-mediated mitochondrial fission results in mitochondrial stress and the release of mtDNA in the cytosol [116].…”
Section: Interference With the Cgas/sting Pathwaymentioning
confidence: 99%
“…Several studies have shown that some retroviruses including HIV, murine leukemia virus, and simian immunodeficiency virus can induce a type I IFN response due to recognition of reverse-transcribed DNA by cGAS and subsequent production of cGAMP (Gao et al, 2013a; Lahaye et al, 2013; Rasaiyaah et al, 2013). DENV can antagonize STING signaling by utilizing viral NS2B3 proteases to bind and cleave human STING although this cleavage does not occur in mouse or nonhuman primate STING (Aguirre and Fernandez-Sesma, 2017; Aguirre et al, 2012; Stabell et al, 2018; Yu et al, 2012). HCV has also been shown to antagonize STING signaling, highlighting the multifaceted role of STING in pathogen evasion beyond direct DNA sensing through cGAS (Ding et al, 2013; Maringer and Fernandez-Sesma, 2014; Moriyama et al, 2007; Nitta et al, 2013).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%